2019
DOI: 10.1002/ese3.344
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental and numerical investigations on pressure pulsation in a pump mode operation of a pump as turbine

Abstract: Hydropower has been the leading renewable source and cheapest ways to generate electrical energy in the world. In recent years, there has been a major upsurge in the hydropower development because of the use of pump as turbine (PAT). However, the operational reliability of a PAT is greatly affected by the unsteady flow fields; therefore, it is important to examine the unsteady flow behavior which can be used as a reference to reduce the noise, vibration, and cavitation performance for centrifugal pumps working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 24 publications
(47 reference statements)
0
19
0
Order By: Relevance
“…For pressure pulsation in centrifugal pumps, two topics are mainly discussed, namely the generating mechanism and the corresponding control. RSI resulted by the impeller periodically sweeping the tongue is the primary factor accounting for high and intense pressure pulsations in centrifugal pumps, which is investigated and validated by many researchers [6,7]. Pressure spectral characteristics at different working conditions were clarified.…”
Section: Introductionmentioning
confidence: 92%
“…For pressure pulsation in centrifugal pumps, two topics are mainly discussed, namely the generating mechanism and the corresponding control. RSI resulted by the impeller periodically sweeping the tongue is the primary factor accounting for high and intense pressure pulsations in centrifugal pumps, which is investigated and validated by many researchers [6,7]. Pressure spectral characteristics at different working conditions were clarified.…”
Section: Introductionmentioning
confidence: 92%
“…3 Because of its simple structure, low cost, reliable performance, and convenient maintenance, centrifugal pumps are widely used as turbines. [4][5][6][7] The current research on the internal flow of PAT includes: speed slip mechanism, 8,9 noise, 10,11 pressure pulsation [12][13][14][15][16][17][18][19][20] and energy conversion characteristics. 21 Literature 9 used different turbulence models to perform numerical calculations on PAT and found that the it has a velocity slip phenomenon, which causes the turbine head to decrease and induces vortices attached to the blade working surface.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [17] completed numerical analysis on the reduction of pressure pulsation for a double-section centrifugal pump and proposed that a combination of multi-blades, a larger radial gap, and staggering arrangements can reduce the pressure pulsation inside the pump. Zhang et al [18] explored the pressure pulsation in a nuclear reactor coolant pump. It was confirmed that pressure pulsation acting on the impeller's blade is mainly dominated by the impeller rotating frequency, the vane passing frequency, and the double blade-passing frequency, and the pressure pulsation acting on the blade's pressure surface is more intense than on the suction surface.…”
Section: Introductionmentioning
confidence: 99%